A comprehensive review on pre-treatment strategy for lignocellulosic food industry waste: Challenges and opportunities. (January 2016) - Ravindran, Rajeev; Jaiswal, Amit Kumar
Abstract : Graphical abstract: Abstract : Highlights: Factors influencing the effective valorization of lignocellulose. Classification of pretreatments with detailed description of various strategies. Physical, Chemical, Biological and Physico-chemical pretreatment of lignocellulose. Formation of inhibitory compounds post pre-treatment of lignocellulose. Strategies for effective removal of inhibitory compounds. Abstract: Lignocellulose is a generic term used to describe plant biomass. It is the most abundant renewable carbon resource in the world and is mainly composed of lignin, cellulose and hemicelluloses. Most of the food and food processing industry waste are lignocellulosic in nature with a global estimate of up to 1.3 billion tons/year. Lignocellulose, on hydrolysis, releases reducing sugars which is used for the production of bioethanol, biogas, organic acids, enzymes and biosorbents. However, structural conformation, high lignin content and crystalline cellulose hinder its use for value addition. Pre-treatment strategies facilitate the exposure of more cellulose and hemicelluloses for enzymatic hydrolysis. The present article confers about the structure of lignocellulose and how it influences enzymatic degradation emphasising the need for pre-treatments along with a comprehensive analysis and categorisation of the same. Finally, this article concludes with a detailed discussion on microbial/enzymatic inhibitors that arise post pre-treatment and strategies to eliminate them.